Development of problem-based learning mathematics modules to enhance students' mathematical problem-solving skills - Maharani, Lola Amelia; Heleni, Susda; Syofni (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This research aims to develop a mathematics module based on Problem-Based Learning (PBL) for straight-line equation material, designed to enhance students' mathematical problem-solving skills at SMP Negeri 1 Pasir Penyu. The study employed a Research and Development approach, utilizing a 4-D development model that includes the stages of Define, Design, Develop, and Disseminate. The subjects were eighth-grade students at SMP Negeri 1 Pasir Penyu. Data collection instruments included validation sheets to evaluate the module's validity and student response questionnaires to assess its practicality. The module was tested in two phases: a small group trial and a large group trial. Results from the small group trial indicated that the module achieved an average score of 3.66, categorizing it as highly practical. Similarly, the large group trial yielded an average score of 3.57, also placing the module in the very practical category.